Design of a Samier Cracker Dough Molding Machine Semi-Automatic with Roll Cutting Method: Rancang Bangun Mesin Cetak Adonan Kerupuk Samier Semi-Otomatis dengan Metode Roll Cutting - Prasetiyo, Abdul Aziz; Akbar, Ali; Tjahjanti, Prantasi Harmi (Procedia of Engineering and Life Science, 2023)
The main obstacle that UMKM SA has is limited production technology which is still manual so that workers take a long time and production results are not good because the thickness of the crackers is uneven and the sizes cannot match. So it is necessary to design a cracker-making machine by making a printing roll tool. The design method uses the manufacturing process method which is based on the cutting process and has a different perspective from the previous thing. Where the researcher analyzes the advantages and disadvantages of the product to be made, has an overview of the product to be made by taking samples of material sources and data from the analysis that has been carried out directly to the resource persons as well as by analyzing the processes that have been carried out. The results of the study are from data analysis of the cracker dough cutting machine with the selected concept, it can be said to be effective with a faster time record in each test, good efficiency and effectiveness of the first tool requires an average time of 03:80 to 01:12 with cracker dough size 46x46x1 totaling 121 pieces.